Особенности морфологии жуков-чернотелок (Coleoptera, Tenebrionidae) фауны Украины - Черней, Л.С.; Прохоров, А.В.; Белов, А.А. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Приведены оригинальные данные по морфологии жуков-чернотелок, которые станут основой для выяснения вопросов эволюции и филогении семейства, а также будут использованы для построения современных определителей. Изучены 102 вида, относящиеся к 54 родам и 29 трибам жуков-чернотелок, обитающих на территории Украины. Original data on the morphology of tenebrionid beetles are presented and discussed. These data can be used to distinguish the questions of evolution and phylogeny of the family Tenebrionidae. New morphological characters can be used for modern identification keys of darkling beetles. One hundred two species belonging to 54 genera and 29 tribes of darkling beetles of the fauna of Ukraine were studied.